Pendampingan Pendirian Koperasi Merah Putih di Lembang Tondon Langi, Toraja Utara - Winta Panimba; Wilma Dian Ardiyanti; Srisetyawani Bandaso; Yohanis Lotong Ta’dung; Marinus Ronal (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity was implemented with an educational and participatory approach through outreach activities, lectures, discussions, and intensive mentoring. This activity was aimed at participants in the meeting to establish the Merah Putih Village Cooperative, consisting of various elements of the community, Lembang officials, and several representatives from related sectors who have a direct or indirect relationship with village economic development through cooperatives. The material provided included an understanding of the basics of cooperatives, the benefits of the existence of cooperatives for village communities, as well as the stages or legal and administrative flows in the process of establishing a cooperative in accordance with applicable regulations in Indonesia. In addition, participants were also given insight into the principles of good cooperative governance, financial transparency, member meeting mechanisms, and the distribution of SHU (Surplus Operating Results) fairly and proportionally. The material was delivered through interactive lectures and open discussions that allowed for active participant participation to ask questions, provide suggestions, and express their experiences and hopes for the cooperative that will be formed. The activity continued with mentoring in the process of establishing the cooperative's organizational structure, including the election of administrators, the preparation of AD/ART, and understanding the duties and responsibilities of each element in the cooperative organization. The primary goal of this mentoring activity is to provide comprehensive understanding, increase community capacity to manage cooperatives independently and professionally, and encourage active community participation in productive economic activities through cooperatives. Thus, it is hoped that the Merah Putih Village Cooperative can become a sustainable driving force for the local economy.